2012
DOI: 10.1007/s12154-012-0072-3
|View full text |Cite
|
Sign up to set email alerts
|

3D-QSAR studies of triazolopyrimidine derivatives of Plasmodium falciparum dihydroorotate dehydrogenase inhibitors using a combination of molecular dynamics, docking, and genetic algorithm-based methods

Abstract: A series of 35 triazolopyrimidine analogues reported as Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH) inhibitors were optimized using quantum mechanics methods, and their binding conformations were studied by docking and 3D quantitative structure-activity relationship studies. Genetic algorithm-based criteria was adopted for selection of training and test sets while maintaining structural diversity of training and test sets, which is also very crucial for model development and validation. Both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[20,21] Moreover, the distance dependence between the probe atom and the molecule atoms was determined by a Gaussian function.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…[20,21] Moreover, the distance dependence between the probe atom and the molecule atoms was determined by a Gaussian function.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The findings yielded revealed that tetrahydroharman isolated from G. senegalensis exhibits antimalarial activity with neither cytotoxicity nor genotoxicity found in Salmonella Ames test, with and without metabolic activation (Azas et al, 2002). Derivatives of triazolopyrimidine (Shah et al, 2012) Modelling the evolution of drug resistance in malaria.…”
Section: Natural Productsmentioning
confidence: 99%
“…44 This method guarantees that the prediction set spans the entire range of the experimental measurements and is numerically representative of the dataset. 45,46 2.5 Chemical structure optimization and alignment Molecular modeling and database alignment were performed by using the SYBYL 6.9 program package. 47 3D structures of all compounds were constructed using the Sketch Molecule module.…”
Section: Splitting the Dataset Using Som And Random Approachesmentioning
confidence: 99%